Guarantee of the Franchise Contract: An Analytical Study - Aidh Sultan Albaqme (International Journal of Law Research and Studies, 2025)
Commercial franchise contracts (franchises) are important and modern contracts that are primarily concerned with the marketing of goods and services. They first originated in the United States of America and were then used by American companies on an international scale. Their use became widespread in many countries, as these contracts represent an effective means of transferring technical knowledge and production projects in a manner that achieves the objectives of the contracting parties and thus benefits them, providing the franchisor with an excellent opportunity for rapid expansion without placing a financial burden on its capital expenditures, as well as providing it with the opportunity to quickly access markets. This contract is defined as follows: “A contract whereby the first party (the franchisor) grants the second party (the franchisee) the right to use intellectual property rights (trade name, trademark, patent) and technical knowledge for the production of goods, distribution of products, and provision of services to the second party (the franchisee) to enable them to start commercial activity and perform work in the franchise area.” This contract is of great importance as a tool that helps economic and commercial growth and a means of attracting investments that bring advanced technology, as it contributes to providing job opportunities for the national workforce and developing it through the training it receives in the established projects, which contributes to raising the efficiency of the human resources, It also reduces the rate of capital flight abroad, increases investment in medium-sized projects based on successful brands, works to avoid harming national products, and motivates local companies to reorganize themselves so that they can compete, thereby increasing the value of their products offered to consumers. However, There is still ambiguity regarding the limits of responsibility of the parties to the commercial franchise contract as to who bears the guarantee for the goods or Customer-facing service, and this may negatively affect the expansion of this type of contract if the warranty provisions of this contract are not clearly and explicitly stated to the parties to the contract and the legal regulations governing this contract.